2003
DOI: 10.1097/01.nmd.0000051903.60517.98
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity as a Predictor of Symptom Change After Treatment in Combat-Related Posttraumatic Stress Disorder

Abstract: Posttraumatic stress disorder (PTSD) is a difficult condition to treat, and existing studies show considerable variability in outcome. Investigations of factors that influence outcome have the potential to inform alternate treatment approaches to maximize benefits gained from interventions for the disorder. Because PTSD is commonly associated with comorbidity, it is important to investigate the influence of comorbidity on symptom change after treatment. This article examines pretreatment and 9-month follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 24 publications
6
109
0
4
Order By: Relevance
“…In other words, documented associations may represent statistical artifacts given that anger items are present on both the PTSD and anger measure. We are aware of two studies that have directly addressed this question by removing anger-related items from the PTSD measure and examining whether associations were substantially reduced relative to associations involving the full PTSD measure (including anger items): one in a sample of Vietnam combat Veterans [24] and the other in a sample of female crime victims [25]. Both studies demonstrated that associations were virtually unchanged when the angerrelated items were removed from the PTSD measure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, documented associations may represent statistical artifacts given that anger items are present on both the PTSD and anger measure. We are aware of two studies that have directly addressed this question by removing anger-related items from the PTSD measure and examining whether associations were substantially reduced relative to associations involving the full PTSD measure (including anger items): one in a sample of Vietnam combat Veterans [24] and the other in a sample of female crime victims [25]. Both studies demonstrated that associations were virtually unchanged when the angerrelated items were removed from the PTSD measure.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Forbes et al examined the influence of anxiety, depression, anger, and alcohol use on symptom change among Vietnam Veterans in treatment for PTSD [24]. Veterans were assessed at pretreatment and again 9 months after treatment concluded.…”
Section: Methodsmentioning
confidence: 99%
“…Military-related posttraumatic stress disorder (PTSD) occurs in a significant minority of veterans and often presents with complex psychiatric co-morbidity (Kessler et al, 1995, Keane and Kaloupek, 1997, Keane and Wolfe, 1990, Forbes et al, 2003, Kulka et al, 1990, Sareen et al, 2004. Twelve month and lifetime prevalence rates of PTSD in the Canadian Regular Forces has been reported as 2.8% and 7.2% respectively (Statistics Canada, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that military-related PTSD is more prone to somatisation (McFarlane et al, 1994) and is associated with more physical health problems (Boscarino, 1997, Boscarino and Chang, 1999, Schnurr and Jankowski, 1999, Sledjeski et al, 2008, Jakupcak et al, 2008, Sareen et al, 2007. Evidence also shows that PTSD is often associated with significant comorbidity including major depression, substance abuse, suicidality, (Kessler et al, 1995, Keane and Kaloupek, 1997, Keane and Wolfe, 1990, Forbes et al, 2003, Kulka et al, 1990, Gradus et al, 2010, Nepon et al, 2010, Sareen et al, 2005 and chronic disability contributing to impaired quality of life (Mills et al, 2006, Richardson et al, 2008, Richardson et al, 2010. Military personnel are more likely to be exposed to trauma than the general public (Breslau et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Anger problems are associated with a number of negative consequences including poor family functioning (Evans, McHugh, Hopwood, & Watt, 2003;Taft, Schumm, Panuzio, & Proctor, 2008), negative workplace and school outcomes (Chen & Spector, 1992;Frueh, Henning, Pellegrin, & Chobot, 1997;Hershcovis et al, 2007;Inness, Leblanc, & Barling, 2008;O'Neill, Vandenberg, Dejoy, & Wilson, 2009;Struthers, Miller, Boudens, & Briggs, 2001; S. P. Thomas & Smith, 2004), aggression (Taft, Street, Marshall, Dowdall, & Riggs, 2007;Teten et al, 2010), and poorer treatment outcomes for posttraumatic stress disorder (PTSD) (Forbes et al, 2005; Creamer, Hawthorne, Allen, & McHugh, 2003;Forbes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%